Geotechnical investigation of the relationship between physical properties and saturated hydraulic conductivity by using the empirical formulas - Kannangara, Dumal; Sarukkalige, Priyantha; Botte, M (Research Publishing Services, 2012)
Historically geologists, engineers, and soil scientist have conducted many field and laboratory tests to find the best soil permeability values for their design, identifying the fundamental relationships between the soil properties and the soil permeability it still remains inadequately quantified. As the soil permeability changes from one place to another, even in the same soil type and the same horizontal profile, the determination of the correct soil permeability value has become more challenging. Many different techniques have been proposed to quantify the hydraulic conductivity including several empirical formulas. Most of the empirical formulas overestimate the value of soil permeability even in the same soil sample and some of the values are not directly applicable in a physical environment due to the theoretical enforced limitations. However, accurate estimation of soil permeability in the field environment by the field methods is also limited by the lack of precise knowledge and equipment and the cost of any additional field operations involved. Therefore this case study was focused on identifying the most effective soil parameters which govern the value of saturated hydraulic conductivity and to check the applicability and the reliability of comparing the use of existing empirical formulas to the experimental test results.